2014
DOI: 10.1080/19768354.2014.881917
|View full text |Cite
|
Sign up to set email alerts
|

The effects of Korean mistletoe extract on endurance during exercise in mice

Abstract: Many investigators have screened drugs and foods for the enhancement of endurance capacity and antifatigue. Mistletoe, a semiparasitic plant on various deciduous trees, has many known biological activities, including anticancer, anti-diabetes, antioxidant, and anti-cardiovascular disease effects. In a previous study, Korean mistletoe extract (KME) was reported to increase endurance capacity in mice. However, whether the administration of KME further enhances exercise performance, when combined with exercise tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…Mistletoe extract stimulates the release of peroxisome proliferator-activated receptor gamma coactivator 1-alpha and sirtuin 1 in myoblasts, resulting in improved endurance by upregulating mRNA expression of genes associated with mitochondrial creation and function [ 24 ]. It has also been shown to increase expression of mitochondrial uncoupling protein-3 in a myoblast cell line, which activates adenosine monophosphate-activated protein kinase (AMPK) [ 31 ]. Another animal study on mistletoe extract supplement enhancement of endurance reported that administration of mistletoe extract for 12 weeks extended time to exhaustion on the treadmill by 2.5 times and swimming time by 212% and reduced postexercise lactate levels in the experimental group compared to the control group [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mistletoe extract stimulates the release of peroxisome proliferator-activated receptor gamma coactivator 1-alpha and sirtuin 1 in myoblasts, resulting in improved endurance by upregulating mRNA expression of genes associated with mitochondrial creation and function [ 24 ]. It has also been shown to increase expression of mitochondrial uncoupling protein-3 in a myoblast cell line, which activates adenosine monophosphate-activated protein kinase (AMPK) [ 31 ]. Another animal study on mistletoe extract supplement enhancement of endurance reported that administration of mistletoe extract for 12 weeks extended time to exhaustion on the treadmill by 2.5 times and swimming time by 212% and reduced postexercise lactate levels in the experimental group compared to the control group [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The above mentioned blood LDH and CK are indirect indicators of cell damage [ 32 ]. In contrast, lipid peroxidation directly reflects the oxidative damage of cell membrane, which also contributes to the pathophysiology of fatigue [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Korean mistletoe treatment increased the expression of PGC-1α transcriptional targets, such as PGC-1β, NRF-1 (nuclear respiratory factor-1), ERRα (estrogen-related receptor α), Tfam (mitochondrial transcription factor A), PPARβ/δ (peroxisome proliferator-activated receptor β/δ), MB (myoglobin) and TNNI2 (troponin I) in C2C12 cells. Additionally, Korean mistletoe decreased levels of plasma lactate and lactate dehydrogenase, parameters of tissue damage and muscle fatigue in exhausted mice (Jung et al 2012;Lee et al 2014). Furthermore, exercise training increases the muscular glycogen and plasma free fatty acid (FFA) level, and Korean mistletoe administration increased the plasma FFA level, indicating that Korean mistletoe administration alters the energy resources in muscle (Lee et al 2014).…”
Section: Muscle Mitochondrial Activitymentioning
confidence: 99%
“…Additionally, Korean mistletoe decreased levels of plasma lactate and lactate dehydrogenase, parameters of tissue damage and muscle fatigue in exhausted mice (Jung et al 2012;Lee et al 2014). Furthermore, exercise training increases the muscular glycogen and plasma free fatty acid (FFA) level, and Korean mistletoe administration increased the plasma FFA level, indicating that Korean mistletoe administration alters the energy resources in muscle (Lee et al 2014).…”
Section: Muscle Mitochondrial Activitymentioning
confidence: 99%
See 1 more Smart Citation